2013
DOI: 10.1021/jm401075x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Class of Dimeric Smac Mimetics as Potent IAP Antagonists Resulting in a Clinical Candidate for the Treatment of Cancer (AZD5582)

Abstract: A series of dimeric compounds based on the AVPI motif of Smac were designed and prepared as antagonists of the inhibitor of apoptosis proteins (IAPs). Optimization of cellular potency, physical properties, and pharmacokinetic parameters led to the identification of compound 14 (AZD5582), which binds potently to the BIR3 domains of cIAP1, cIAP2, and XIAP (IC50 = 15, 21, and 15 nM, respectively). This compound causes cIAP1 degradation and induces apoptosis in the MDA-MB-231 breast cancer cell line at subnanomola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 55 publications
4
67
0
Order By: Relevance
“…Additionally, Foster et al demonstrated in breast cancer cell lines that the use of a combination of IAP antagonists with proapoptotic agents promotes apoptosis, suggesting that this combination of drugs could offer a clinical benefit in breast cancer patients [23]. Recently published study by Hennessy et al, conducted in cell lines and in breast cancer patients, indicated that the novel dimeric IAP antagonist -compound 14 (AZD5582) is promising candidate for clinical development as an anticancer agent [25].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Foster et al demonstrated in breast cancer cell lines that the use of a combination of IAP antagonists with proapoptotic agents promotes apoptosis, suggesting that this combination of drugs could offer a clinical benefit in breast cancer patients [23]. Recently published study by Hennessy et al, conducted in cell lines and in breast cancer patients, indicated that the novel dimeric IAP antagonist -compound 14 (AZD5582) is promising candidate for clinical development as an anticancer agent [25].…”
Section: Discussionmentioning
confidence: 99%
“…As drawn, the monomeric units of BV6 [81] and SM-164 [83] appear to point away AstraZeneca disclosed a family of P4-P4 compounds that were linked through the P4 amide moity [99]. These studies lead to the nomination of the clinical candidate AZD5582 [100].…”
Section: Bivalent P4-p4 Iap Inhibitorsmentioning
confidence: 99%
“…Binding to cIAP1 and cIAP2 induces E3 ubiquitin ligase activity resulting in ubiquination of RIPK1, canonical NF-κB activation, cIAP1 and cIAP2 autoubiquitination, and their subsequent proteasomal degradation [78,79]. Therefore, loss of cIAP1 protein from cellular lysates and clinical samples has served as an effective biomarker during both preclinical and clinical development [1][2][3][4][5][6][7][8]34,35,44,70,95,96,100,110]. As such, both singleagent and combination trials are ongoing.…”
Section: Clinical Compoundsmentioning
confidence: 99%
“…Both 15 and 16 have good activity against the type I cancer cell lines, and we observed sub-μM IC 50 values against type II A875 cells. More benefit was observed with L-cyclohexylglycine (17) or L-tert-butylglycine (18) in P2 while retaining L-2-naphthylalanine in P4. Potent binding affinity of these compounds for BIR2 and 3 domains translated into inhibition of both XIAP and cIAP1 BIR2−3 constructs tested in a FPA format.…”
Section: ■ Introductionmentioning
confidence: 96%